Las troyanas - Eurípides 480 a.C.- 406 a.C (Colección Pensamiento)
Introducción -- Las troyanas -- Escena I -- Escena II -- Escena III -- Escena IV -- Escena V -- Escena VI -- Escena VII -- Escena VIII -- Escena IX -- Escena X -- Escena XI -- Escena última -- Guia de trabajo.